Effects of sowing date and nutsedge removal time on plant growth and yield of tef [Eragrostis tef (Zucc.) Trotter] - Juraimi, Abdul Shukor; Begum, Mahfuza; Sherif, Ahmed Mohammed; Amarthalingam, Rajan (Academic Journals, 2009)
Tef [Eragrostis tef (Zucc.) Trotter] is an annual C4 grass crop that originated in Ethiopia. The average grain yield of this crop is low; averaging < 0.8 Mg ha-1 in farmer's fields of the semi arid conditions. Productivity can be increased to a considerate extent through the improvement of management practices alone, particularly sowing time with appropriate weed control. The objective of this study was to identify the growth and yield performance of tef as affected by cultural manipulation of date of sowing and weed removal time at semi arid region in Alem tena in Ethiopia. Tef was planted at three sowing dates, recommended sowing date, 7 and 15 days delay after the recommended date. The five weed removal time were included as weedy check (W1), weeded two weeks (W2), four weeks (W3), six weeks (W4) after crop emergence and weed-free check (W5). All data were subjected to analysis by ANOVA, principal component analysis (PCA) and correlation/regression analysis. Weed removal time played a minor role compared to sowing time. Irrespective of weeding dates, delayed tef sowing time was very critical. Plant height reduced by 23 to 32%, panicle length by 45.51 and 55.11% crop biomass by 34.39 and 35.53% and grain yield 60 to 68%, when sowing was delayed for 7 and 15 days, respectively. The relationship between plant height and grain yield and crop biomass and grain yield of tef was very strong and quadratic, whereby, as the plant height as well as crop biomass increased, the yield also increased. All these relationships clearly indicate the high competitive ability of tef against nutsedge. Nutsedge competition during the first 6 weeks after crop emergence reduced tef biomass by more than 30%. Keeping the tef field free of weeds for at least six weeks for early and late sown tef is essential to give the crop advantage of growing faster to enhance crop yields.